A Study Of The Capacity Of Nigerian Universities For Hosting Online Guidance And Counselling Services - Adeniyi, Victor Adewale (Advances in Social Sciences Research Journal, 2019)
The study determined the availability and adequacy of facilities for Online Guidance and Counselling Services (OGCS) among Universities in Southwestern Nigeria and assessed the adequacy and competence of existing personnel for OGCS in the universities. The study adopted a survey research design. A sample of 108 staff members was selected using multi-stage sampling technique. The stratified sampling technique was used to select three out of the six states that make up Southwestern Nigeria. University staff Assessment of institutional Capacity for Online Guidance and Counselling Services (USAICOCS) A Checklist and Interview Guide (CAIG) and level of adequacy and competency of existing personnel for OGCS Questionnaire (LACPQ) were used to collect data for the study. The results showed that facilities for hosting OGCS such as internet, computer and electricity were available (more than 60%). However, most of the other needed facilities such as online counselling platform application and counselling system data base recorded less than 50% of the minimum required. The availability of the facilities was therefore adjudged inadequate. The results also showed that the personnel for OGCS were grossly inadequate. None of them had ever handled OGCS equipment. The results further showed that the ICT section of each university had enough personnel that could set up the OGCS platform.